2012
DOI: 10.1001/archsurg.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopy on the Risk of Small-Bowel Obstruction

Abstract: To investigate the incidence and risk factors for small-bowel obstruction (SBO) after certain surgical procedures. Design: A population-based retrospective register study. Setting: Small-bowel obstruction causes considerable patient suffering. Risk factors for SBO have been identified, but the effect of surgical technique (open vs laparoscopic) on the incidence of SBO has not been fully elucidated. Patients: The Inpatient Register held by the Swedish National Board of Health and Welfare was used. The hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The findings of this study are similar to those in other reports4 15. One15 of these studies reported that after 10 years the need for further operation for adhesive SBO was 7 per cent (5 of 74 patients) following open rectal resection versus 0 per cent (0 of 74) after laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings of this study are similar to those in other reports4 15. One15 of these studies reported that after 10 years the need for further operation for adhesive SBO was 7 per cent (5 of 74 patients) following open rectal resection versus 0 per cent (0 of 74) after laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 90%
“…One15 of these studies reported that after 10 years the need for further operation for adhesive SBO was 7 per cent (5 of 74 patients) following open rectal resection versus 0 per cent (0 of 74) after laparoscopic surgery. The other report4 examined the risk of surgery for SBO including adhesive SBO following rectal resection in a Swedish population‐based study. Among 3523 patients undergoing anterior resection, the 5‐year risk of SBO or adhesive SBO after open anterior resection was 2·8 per cent, compared with 1·6 per cent after laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential advantages of the minimally invasive approach to small intestinal neoplasm resection include comparable surgical and oncologic outcomes [ 3 , 25 , 26 ], decreased length of stay [ 25 -28 ], cosmetically appealing scar, and improved pain scores [ 24 , 28 -31 ]. In addition, when compared with open operations there is a decrease in incisional hernia occurrence, diminished adhesion formation with a presumed lower postoperative bowel obstruction incidence [ 32 ]. All of these advantages should translate to improved patient satisfaction with a decrease in overall health care costs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%